O patrimônio do riso na arte da palhaçaria - Gonçalves, Deivide Millani (2022)
This master's thesis work in cultural heritage aims to share the production of a booklet of clown games, using the universal language of the clown, this language considered from my experiences and practices, to be used by different groups, such as: educators, artistic, systematizing a learning that was only gestural, oral and traditional. Based on intangible heritage culture, this research addresses the origin of man's comedy, making a chronological narrative, from its beginning, to the use of terminologies referenced to the figure that we know today as "Clown" or "Clown" and also dialogues with the concept heritage, memory and orality, which are the main bases of continuity and propagation of this artistic work. Finally, with this work, we seek to create opportunities for contact with artistic work and encourage heritage education, as well as the preservation and maintenance of the clown's artistic work.